Penyegaran Kader dan Pelayanan Posbindu - Asda, Patria; Syarifah, Nur Yeti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2022)
prevalence rate of non-communicable diseases in the 2018 based on National Basic Research on public’s results has increased compared to the results of Nasional Basic research in 2013. Cepit Pendowoharjo Hamlet has many residents who suffer from non-communicable diseases such as hypertension, gout and cholesterol. The activities of the Posbindu in the Cepit village have not been carried out continuously and regularly every month. There are still many cadres, especially new cadres who do not understand the mechanism and stages of implementing posbindu. The purpose of this community service activity is to increase the knowledge of cadres and reactivate posbindu’s activities in Cepit Hamlet, Pendowoharjo Bantul. Community service activities were carried out in December 2019, in the form of counseling to cadres in the form of a review of posbindu materials and posbindu services to the community. Materials for cadres are given using audiovisual media in the form of PPT and video. Posbindu services are carried out with a 5 table system. Participants seemed enthusiastic in following the entire agenda of activities. There is an increase in the knowledge of cadres after being given material about the stages of posbindu and the posbindu services to the community have been given well.